(untitled) (BEOIBERÍSTICA - Journal of Iberian, Latin American and Comparative Studies (ISSN: 2560-4163 Online), 2018)
Melancholy is part of the soul of the human being. It is projected in any vital women and men areas of the culture, especially in the field of literature. Western melancholy has been deeply studied and profusely analyzed, but the same has not happened with Andean melancholy. After the Conquest of America by the Spanish conquerors, the Andean soul fell in a lake of sadness. In this paper we try to show the brightness of the Andean heart. The selection of the poem «Hymn to Manko Kapac» is a homage to Peruvian indigenous culture. The intrinsic melancholy, many centuries later, will give wings to the creative talent of the brilliant poet César Vallejo. The wonderful poetry of this author continues the line shown by its predecessors: the first Andean poets who wrote «Hymn to Manko Kapac». Key words: Andean culture, poetry, indigenism, Manko Kapac, melancholy.